China's outward FDI and environmental sustainability in belt and road countries: does the quality of institutions matter?. Issue 5 (16th April 2023) - Kamal, Muhammad Abdul; Ullah, Assad; Qureshi, Fiza; Zheng, Jiajia; Ahamd, Manzoor
Abstract : This study aims to unravel the environmental effects of institutional quality in relationship with China's Foreign Direct Investment (FDI) in Belt and Road Initiative (BRI) countries. The empirical analysis is conducted over the period 2003–2018, using the System-GMM approach with the Windmeijer finite-sample correction. We infer that China's FDI has a detrimental effect on environmental quality, which validates the 'pollution haven hypothesis' in the BRI region. Importantly, the interaction effect of China's FDI with indicators of institutional quality yields negative and significant results. This entails that strong institutions can boost the quality of the environment through FDI attractiveness. In further assessment, the threshold levels of institutional quality are calculated, beyond which China's FDI can reduce carbon emissions in the BRI region. This substantiates both the pollution haven and pollution halo hypotheses. The study underscores the importance of institutional reform in the quest for sustainable development, owing to the fact that most economies prioritize FDI-led growth strategies.